2015
DOI: 10.4103/0974-9233.159692
|View full text |Cite
|
Sign up to set email alerts
|

Complications of strabismus surgery

Abstract: All surgeries carry risks of complications, and there is no way to avoid ever having a complication. Strabismus surgery is no different in this regard. There are methods to reduce the risk of a complication during or after surgery, and these steps should always be taken. When a complication occurs, it is important to first recognize it and then manage it appropriately to allow for the best outcome possible. This article will discuss some of the more common and/or most devastating complications that can occur d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 17 publications
0
18
0
1
Order By: Relevance
“…Changes in refractive error have been noted in several studies but the results were debatable. 11 Horizontal strabismus surgery has been shown to affect corneal topography. 1 This study observed the effect of two different techniques: single lateral rectus (LR) recession in group A and medial rectus (MR) resection with LR recession in the same eye in Group B.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in refractive error have been noted in several studies but the results were debatable. 11 Horizontal strabismus surgery has been shown to affect corneal topography. 1 This study observed the effect of two different techniques: single lateral rectus (LR) recession in group A and medial rectus (MR) resection with LR recession in the same eye in Group B.…”
Section: Discussionmentioning
confidence: 99%
“…Rates of scleral perforation have been reported in 2.8% of strabismus surgeries, which may be an underestimation since many patients are evaluated for this complication only if the surgeon subjectively senses that the needle has advanced too deep. 1,2 Scleral perforations have been associated with serious ocular sequelae, including retinal detachment and endophthalmitis. 3 …”
Section: Introductionmentioning
confidence: 99%
“…Horizontal rektus kasının skleraya direkt sütüre edilmesi sonrası klinik önemi her olguda bilinmemekle beraber %0,4 ile %2,8 arası oranlarda retinada mikroperforasyonlar bildirilmiştir (6) . Bunun yanında, maksimum cerrahi planlanan olgularda kasın insersiyon yerinden çok geriye sütüre edilmesi teknik olarak zor olduğu gibi, konjonktivada istenmeyen yırtıklara ve kontrolsüz cerrahiye neden olabilmektedir (7) .…”
Section: Introductionunclassified